Agro-morphological and genetic variability analysis in oat germplasms with special emphasis on food and feed. - Raj Kumar; Smriti Varghese; Deepanshu Jayaswal; Kuldip Jayaswall; Kuldeep Yadav; Gaurav Mishra; R P Vyas; H C Singh; H G Prakash; Arvind Nath Singh; Sanjay Kumar (PLoS ONE, 2023)
The gaining attention of underutilized oat crops for both food and feed, mining of quality and yield related genes/QTLs from available germplasms of oat is need of the hour. The large family of grasses has a vast number of germplasms that could be harnessed for bio-prospecting. The selection of cross-compatible oat germplasms by molecular markers could be used for the introgression of the novel traits into the elite background of oats. The process needs a thorough study of genetic diversity to see the evolutionary relatedness among germplasms. Considering this, in the present study, the genetic diversity of 38 oat germplasms with 12 agro-morphological traits was carried out using 22 Inter Simple Sequence Repeat (ISSR) markers. We found a high level of polymorphism and 158 distinctive alleles; on average 7.18 alleles per primer, further, high-yielding genotypes were identified with the help of phenotypic data and genetic diversity was analyzed by using DNA fingerprint-based principal component analysis, UPGMA dendrogram. Among these 38 germplasms; eight were identified as superior under high grain yield (OS-424, OS-403, NDO-1101, OL-10, UPO-212, OS-405, OS-6, and OS-346) and another eight germplasms were identified as superior for the high fresh weight (for fodder purpose, NDO-711, RO-19, OL-14, OL-1760/OL-11, NDO-10, UPO-212, UPO-06-1, and RO-11-1). These results suggest that germplasms that are closely related (Cross-compatible) and have good potential for desirable traits could be used for varietal development by using marker-assisted selection.